Managing the Risks of Proactivity: A Multilevel Study of Initiative and Performance in the Middle Management Context - Glaser, Lotte; Stam, Wouter; Takeuchi, Riki (Academy of Management Journal, 2016)
Drawing on theories of behavioral decision making and situational strength, we developed and tested a multilevel model that explains how the performance outcomes of personal initiative tendency depend on the extent of alignment between organizational control mechanisms and proactive individuals’ risk propensities. Results from a sample of 383 middle managers operating in 34 business units of a large multinational corporation indicated that risk propensity weakens the positive relationship between personal initiative tendency and job performance. This negative moderating effect was further amplified when middle managers receive high job autonomy but was attenuated in business units with a strong performance management context. We discuss the implications of these findings for research on proactivity, risk taking, and organizational control.